Newspaper vs. online advertising: Is there a niche for newspapers in modern advertising markets? - Nadine Lindstädt; Oliver Budzinski (University of Southern Denmark, Department of Environmental and Business Economics (IME), 2011)
Newspapers have experienced declining circulation figures and declining advertising revenues for several years. In particular, declining advertising figures put a threat on newspapers - this is especially severe in the US where 73% of their revenues are generated through advertising. On the advertising side many companies have expanded their advertising expenditure towards online. Consequently, there are concerns about online advertising substituting newspaper advertising - in the same way as it has been feared for many years for the readership side. Both possible effects might put a threat on the further existence of (print) newspapers. However, though the internet - compared to newspapers - offers a variety of advantages for advertising companies, substitution tendencies cannot be generalized. In particular, we argue that newspaper advertising offers great benefits for the retailing industry. Consequently, we believe that retail advertising offers a niche for regional and local newspapers that can be expected to represent a sustainable segment of complementarity within the otherwise predominantly substitutional advertising markets. The paper substantiates this argument by applying the economic theory of advertising - in particular the differentiation between persuasive/complementary and informative advertising. The latter one presents the reason for retailers to continue advertising in newspapers. Subsequently, we conclude that no complete substitution between newspaper and online advertising can be expected to take place on the advertising side in the foreseeable future.
Keywords: L82; A20; L13; M21; 330; media economics; advertising; competition; complementation; substitution; online; Werbeträger; Zeitungswerbung; Online-Marketing; Vertriebsweg; Wettbewerb; Medienökonomik